The Effect of Mindset and Income Expectations on Students’ Entrepreneurial Motivation in Depok and Bogor - Zahrotun Nur Hasanah; Ni Made Widhi Sugianingsih; Meisa Sofia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Entrepreneurial motivation among university students has become an important issue in addressing employment challenges and promoting future business creation. This study aims to examine the effect of mindset and income expectations on students’ entrepreneurial motivation in Depok and Bogor. A quantitative empirical approach was employed using a survey method involving university students selected through purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression supported by validity, reliability, and classical assumption testing. The findings indicate that mindset has a positive and significant effect on entrepreneurial motivation, demonstrating that cognitive orientation and entrepreneurial thinking patterns encourage students to pursue business activities. Income expectations also show a positive and significant influence, indicating that anticipated economic benefits strengthen entrepreneurial motivation. The study contributes to entrepreneurship literature by integrating psychological and economic perspectives in explaining student entrepreneurial motivation and provides practical implications for educational institutions in developing entrepreneurial programs that enhance students’ readiness, confidence, and commitment toward entrepreneurship.